Causality Test on Panel Data: An Application to the Study of the Causality Between Agricultural Growth and Demographic Burst in the Uemoa Area - ADEGNIKA, Moutairou (European Journal of Applied Sciences, 2022)
This article aims to analyze the main lines of the modern theoretical debate around the interactions between demographic growth and agricultural growth in the WAEMU space. It identifies the (none) causalities between certain demographic and agricultural growth variables focused on an autonomous and intermediate research field between the corpora of demography and agricultural growth theory. The results of the application of the approach of Konya (2006) based on a test of (none) causality in the sense of Granger (1969), show that the econometric results obtained are ambiguous to the theoretical corpus which was constituted between the strong population growth and weak agricultural growth in the WAEMU space. According to the results of the various (no) tests, the causality between the population surge and agricultural growth is far from being retroactive in certain countries (Benin and Mali) unlike other countries in the area where we note the existence of feedback between population growth and agricultural growth. Almost all the countries of the UEMOA space seem to be part of the logic of the populationists. Population growth in WAEMU countries remains a determining factor for agricultural growth. It is the main lever of agriculture. This result confirms the thesis of Jean Bodin (1530-1596).